IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 78 TAHUN 2010 TENTANG REKLAMASI DAN PASCA TAMBANG DI KABUPATEN KUTAI KARTANEGARA - SOFYANA WIDYA AGUSTIN (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACT Main problem raises at post-mining area is environmental change physically change of morphology and land topoghraphy and degradation of soil productivity with result either infertility or denudation of land. Based on those changing, though reclamation is neede to be done. Despite avoiding erotion reclamation is done to maintain land ffrom instability and making more productive condition. Finally, reclamation is hopefully to yield added value to environment and creating much better condition compared with the past. Surfacial form of post-mining area is generally irregular and mostly as steep morphology. At the time reclamation, steep morphologies are formed to be like as usuall to maintain secured slope condition. Concerning with abandoned mining deposit which have utilitized yet, needed for attention of being potency for either exploitation by public or being managed it in order to avoid decreasing its economic value, also to get back the field like past.Based on the real condition in the district of Kutai Kartanegara, related to Government Regulation Number 78 Year 2010 about Reclamtion and Post-Mining, so reclamation and post-mining constitute important business activities prior to mining activities end. Legislation governing of reclamation and post-mining is in Pasal 96 (c) Undang-Undang Nomor 4 Tahun 2009 about Mineral and Coal Mining and Pasal 2 (1) Government Regulation Number 78 Year 2010 about Reclamation and Post-Mining.Research results from the author of Mining and Energy Services in East Kalimantan Province in Samarinda represented bythe generalminingstaffsection, Mrs. Darlina Manik and Mr. Sukariamat. Manymining companiesthatdo notperformreclamationandpost-mininga challenge forthe district /city. An efforttoaddress concerns andthisconditionisthrough theactivityormine reclamationobligations. So farmine reclamationactivitiesare consideredasa method/most effective effortstoreduce the rate ofenvironmental damage caused byminingactivitiesandcoalminerals Keywords: Reklamasi dan Pasca Tambang